On the Sixth Power Mean Value of the Generalized Three-Term Exponential Sums - Yahui Yu; Wenpeng Zhang (Abstract and Applied Analysis)
The main purpose of this paper is using the estimate for trigonometric sums and the properties of the congruence equations to study the computational problem of one kind sixth power mean value of the generalized three-term exponential sums and give an exact computational formula for it.